Singlet–Triplet Transition Rate Enhancement inside Hyperbolic Metamaterials. Issue 9 (12th August 2019) - Roth, Diane J.; Ginzburg, Pavel; Hirvonen, Liisa M.; Levitt, James A.; Nasir, Mazhar E.; Suhling, Klaus; Richards, David; Podolskiy, Viktor A.; Zayats, Anatoly V.
Abstract: The spontaneous emission process is known to be largely affected by the surrounding electromagnetic environment of emitters, which manifests itself via the Purcell enhancement of decay rates. This phenomenon has been extensively investigated in the case of dipolar transitions in quantum systems, commonly delivering fast decay rates in comparison to forbidden transitions such as high‐order multipolar transitions or spin‐forbidden, singlet–triplet phosphorescence processes. Here, a decay rate enhancement of almost 2750‐fold is demonstrated for a ruthenium‐based phosphorescent emitter located inside a plasmonic hyperbolic metamaterial. The standard electromagnetic local density of states description, typically employed for the Purcell factor analysis of dipolar transitions, is unable to account for a photoluminescence enhancement of this magnitude, which is attributed to the interplay between the local density of states and strongly inhomogeneous electromagnetic fields inside the metamaterial. The large available range of spontaneous emission lifetimes reported here enables application of phosphorescent emitters in novel, fast, and efficient light‐emitting sources, beneficial for optical communications, quantum information processing, spectroscopy, or bio‐imaging. Abstract : The singlet–triplet transition rate enhancement of a phosphorescent complex located in the vicinity of different electromagnetic environments, including a hyperbolic metamaterial, is investigated. It is shown that combining an emitter with spin–orbit coupling and plasmonics leads to significant enhancement of the emission rate, which cannot be accounted for solely by a standard electromagnetic local density of states description.